Seismology of a massive pulsating hydrogen atmosphere white dwarf - Kepler, S. O. (2012)
We report our observations of the new pulsating hydrogen atmosphere white dwarf SDSS J132350.28+010304.22. We discovered periodic photometric variations in frequency and amplitude that are commensurate with nonradial g-mode pulsations in ZZ Ceti stars. This, along with estimates for the star's temperature and gravity, establishes it as a massive ZZ Ceti star. We used time-series photometric observations with the 4.1m SOAR Telescope, complemented by contemporary McDonald Observatory 2.1m data, to discover the photometric variability. The light curve of SDSS J132350.28+010304.22 shows at least nine detectable frequencies. We used these frequencies to make an asteroseismic determination of the total mass and effective temperature of the star: M= 0.88 ± 0.02 M and T eff = 12, 100 ± 140 K. These values are consistent with those derived from the optical spectra and photometric colors.